MARKETING TRANSFORMATION: THE DIGITALIZATION OF WOMEN’S HOME INDUSTRY IN SUNGAI SELAN, CENTRAL BANGKA - Suryadin, Asyraf; Haiyudi, Haiyudi; Widiharjanti, Isti; Ulfiyanti, Tania Nur (Yayasan Education and Social Center, 2025)
The lack of understanding of digital marketing for home industry players is still a major obstacle in developing businesses in Sungai Selan Atas Village, Central Bangka. Therefore, the purpose of this service program is to provide assistance in preparing digital marketing to increase sales of home industry products. In addition, this program also aims to increase the economic value of home industry sales by expanding marketing reach through digital platforms. The method used in this program is training with stages of exposure and practical assistance. The partners in this training were 13 home industry players. Observations and interviews were conducted qualitatively in order to measure behavioral changes for home industry players in Sungai Selan Atas village. After the mentoring process was carried out, it was found that there were changes in behavior and marketing strategies carried out by home industry actors. It is expected that after this assistance is carried out, women home industry players can carry out a sustainable digital sales process to get higher selling value and reach.